A review of the genus Apocepon Nierstrasz & Brender à Brandis (Isopoda: Epicaridea: Bopyridae) parasitic on purse crabs (Decapoda: Brachyura: Leucosiidae) from Chinese waters, with description of a new species - An, Jianmei; Yu, Haiyan; Li, Xinzheng (Zootaxa, 2006)
Description of a new species Apocepon leucosiae sp. nov. of genus Apocepon Nierstrasz & Brender à Brandis, 1930 from Chinese waters, a redescription of Apocepon pulcher Nierstrasz & Brender à Brandis, 1930 from the type locality and the second record of Apocepon digitatum Stock, 1959 are presented. All hosts are in the brachyuran family Leucosiidae. Four purse crab species, i.e. Philyra carinata Bell, Philyra heterograna Ortmann, Leucosia sinica Shen et Chen and Leucosia anatum (Herbst), are recorded for the first time as hosts of parasitic isopods of this genus. A brief differential diagnosis, data on the distribution and a key to the three species in the genus Apocepon are provided.